Transformasi Pengelolaan TPQ Muslimat Kecamatan Klojen Melalui Inovasi program KKM: Penguatan Manajemen dan Media Pembelajaran - HAMDI, AL HILAL (Maliki Interdisciplinary Journal, 2026)
The Student Community Service Program (Kuliah Kerja Mahasiswa/KKM) is a form of community engagement aimed at implementing the Tri Dharma of Higher Education through real contributions to society. This community service activity was carried out by KKM Group 26 students of Universitas Islam Negeri Maulana Malik Ibrahim Malang at TPQ Muslimat 06, Klojen District, Malang City. The purpose of this program was to improve the quality of TPQ institutional management through strengthening financial management and developing learning media. The implementation methods included observation and direct practice in financial management as well as the creation of learning media.The results of the program indicate that the preparation of financial management systems covering budget planning, financial recording and bookkeeping, and systematic financial reporting was able to enhance the accountability of TPQ management. In addition, the development of learning media in the form of Tartila flip charts volumes 1 to 6 had a positive impact on the learning process of hijaiyyah letters, as these media are more practical, engaging, and aligned with the characteristics of the students. Overall, this KKM program made a positive contribution to improving institutional governance and the quality of learning at TPQ Muslimat 06, Klojen District, Malang City.